Highway accelerated loading instrument (HALI) testing on permanent deformation for concrete block pavement - Ling, Tung Chai; Md. Nor, Hasanan; Ming, Fai Chow (2007)
Experiment concrete block pavements (CBP) are essential to study and assess the structural pavement performance. Accelerated loading testing is able to determine the pavement response and performance under a controlled, accelerated, accumulation of damage in a compressed time period. A test was performed in laboratory to investigate the permanent deformation development under Highway Accelerated Loading Instrument (HALI). A CBP model constructed from the bottom with hard neoprene, bedding sand and paving blocks filled with jointing sand was prepared and tested. Up to 2500 cycles load repetitions of a 1000 kg single wheel load were applied to the pavement model. The pavement deformation development was studied through its transverse deformation profile, mean rut depth in the wheel path, longitudinal rut depth profile and joint width between paving blocks. Test results indicated that the rut depth increase with increasing number of load repetitions and also the heaves at each side of the wheel path. It has also shown that the constant deformation, accelerating and braking sections of the pavement have been observed and determined